Les patrimonialisations ordinaires. Essai d’images ethnographiées - Isnart, Cyril (2012)
Ordinary heritagization : an image-based ethnographic essay. This contribution aims at describing and analyzing heritagization processes that are not led by heritage professionals, what could be called “ordinary heritagizations” that are increasing in number throughout Europe. Based on two fieldwork experiences from 2007 to the present — in the city of Rhodes (Greece) and in the village of Tende (France) – the author proposes not a written argument as such but a series of commented photographs, and audio and video recordings. This set of images, sounds and texts are linked by a central question : how do ordinary people construct their heritage ?